\(YX\) domination in bipartite graphs - Y. B. Venkatakrishnan; V. Swaminathan (Scientia, 2025)
A subset \(S\) of \(X\) is called a \(YX\) dominating set if \(S\) is a \(Y-\)dominating set and \(X - S\) is not a \(X\)-dominating set. A subset \(S\) of \(X\) is called a minimal \(YX\) dominating set if any proper subset of \(S\) is not a \(YX\) dominating set. The minimum cardinality of a minimal \(YX\) dominating set is called the \(YX\) domination number of \(G\) and is denoted by \(γ_YX (G)\). In this paper some results on \(YX\) domination number are obtained.